2006
DOI: 10.1002/ajim.20299
|View full text |Cite
|
Sign up to set email alerts
|

Illnesses and injuries reported by Latino poultry workers in western North Carolina

Abstract: Symptoms reported exceeded rates reported by other community, clinical, and occupational samples. Findings suggest policy changes and research are needed to reduce the high rates of occupational illnesses and injuries in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
125
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 20 publications
7
125
4
Order By: Relevance
“…This region has a total of five poultry processing plants belonging to three different companies. With input from a community advisory board, the partnership undertook efforts to document the physical and psychosocial impacts of poultry employment on Latino workers in western North Carolina 4,11,20 and to develop ways of assisting workers individually and collectively in protecting themselves from the demands of this work.…”
Section: The Promoter Programmentioning
confidence: 99%
See 3 more Smart Citations
“…This region has a total of five poultry processing plants belonging to three different companies. With input from a community advisory board, the partnership undertook efforts to document the physical and psychosocial impacts of poultry employment on Latino workers in western North Carolina 4,11,20 and to develop ways of assisting workers individually and collectively in protecting themselves from the demands of this work.…”
Section: The Promoter Programmentioning
confidence: 99%
“…10 Suspected undercounts of injury and illness are corroborated by published studies of Latino poultry processing workers indicating that 60% of workers reported symptoms indicative of work-related illness. 11 Recent congressional hearings on occupational injury and illness undercounts concluded that as much as 69% of injuries and illnesses never find their way into the OSHA statistical summaries. 12 During the past several decades, poultry processing and meatpacking facilities have become concentrated in rural communities, largely in the South.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, improvements in the working conditions have not grown at the same rate as production increased (Sardá et al, 2009). Slaughtering and meat processing work involves high loading intensities and cyclic repetitive muscle actions of the upper limbs, which may represent an elevated risk of work-related musculoskeletal disorders (Quandt et al, 2006;Lipscomb et al, 2008). According to Occupational Safety and Health Administration (OSHA) (2013) risk factors for musculoskeletal disorders (MSDs) in poultry plants are the repetition, forceful exertion, awkward and static postures, vibration, and cold temperatures In consideration to these risk factors, the OCRA checklist was developed to analyze the workers exposure to various risks of developing upper limb work-related musculoskeletal disorders (UL-WMSDs) (strength demand, repetitiveness, inappropriate posture and inadequate movements, lack of recovery periods, and others defined as "complementary") related to activities performed (Colombini and Occhipinti, 2006;Occhipinti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%